2012
DOI: 10.1186/1756-0500-5-59
|View full text |Cite
|
Sign up to set email alerts
|

Splenic injuries at Bugando Medical Centre in northwestern Tanzania: a tertiary hospital experience

Abstract: BackgroundSplenic injuries constitute a continuing diagnostic and therapeutic challenge to the trauma or general surgeons practicing in developing countries where sophisticated imaging facilities are either not available or exorbitantly expensive. The purpose of this review was to describe our own experience in the management of the splenic injuries outlining the aetiological spectrum, injury characteristics and treatment outcome of splenic injuries in our local environment and to identify predictors of outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
57
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(74 citation statements)
references
References 20 publications
15
57
2
Order By: Relevance
“…In agreement with other studies [11,18,20], animal related injuries in our series were found to be most common in the third decade of life. High occurrences of animal related injuries among this age group have been attributed to a wide range of activities engaged in by this class of people.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with other studies [11,18,20], animal related injuries in our series were found to be most common in the third decade of life. High occurrences of animal related injuries among this age group have been attributed to a wide range of activities engaged in by this class of people.…”
Section: Discussionsupporting
confidence: 93%
“…The outcome of treatment of animal related injuries may be poor especially in developing countries due to late presentation, lack of advanced pre-hospital care system and trauma centers and ineffective ambulance system for transportation of patients from the site if injury to hospital continues to be an area of neglect that prevents optimal trauma care [18]. …”
Section: Introductionmentioning
confidence: 99%
“…Subedi et al 26 found that rib fractures were a good indicator of underlying liver and spleen injuries. Ibenzi et al 27 studied patterns of abdominal injury at Muhimbili Hospital and found chest injury as the second most common associated extra-abdominal injury while Chalya et al 28 in Tanzania also found chest injuries (75%) to be the most common associated injury among patients with splenic injuries.…”
Section: Discussionmentioning
confidence: 99%
“…This is due to its close proximity to the abdomen, and some solid organ injuries may be associated with rib fractures. Chalya et al, however, reported that head injury was the most common associated injury (20,21). The presence of associated injuries has been found to be significantly related to increased length of hospital stay and mortality (21).…”
Section: Discussionmentioning
confidence: 99%